Heat-resistant action potentials require TTX-resistant sodium channels NaV1.8 and NaV1.9 - Touska, Filip; Turnquist, Brian; Vlachova, Viktorie; Reeh, Peter W; Leffler, Andreas; Zimmermann, Katharina (The Journal of general physiology, 2018)
Damage-sensing nociceptors in the skin provide an indispensable protective function thanks to their specialized ability to detect and transmit hot temperatures that would block or inflict irreversible damage in other mammalian neurons. Here we show that the exceptional capacity of skin C-fiber nociceptors to encode noxiously hot temperatures depends on two tetrodotoxin (TTX)-resistant sodium channel α-subunits: NaV1.8 and NaV1.9. We demonstrate that NaV1.9, which is commonly considered an amplifier of subthreshold depolarizations at 20°C, undergoes a large gain of function when temperatures rise to the pain threshold. We also show that this gain of function renders NaV1.9 capable of generating action potentials with a clear inflection point and positive overshoot. In the skin, heat-resistant nociceptors appear as two distinct types with unique and possibly specialized features: one is blocked by TTX and relies on NaV1.9, and the second type is insensitive to TTX and composed of both NaV1.8 and NaV1.9. Independent of rapidly gated TTX-sensitive NaV channels that form the action potential at pain threshold, NaV1.8 is required in all heat-resistant nociceptors to encode temperatures higher than ∼46°C, whereas NaV1.9 is crucial for shaping the action potential upstroke and keeping the NaV1.8 voltage threshold within reach.
Keywords: Animals; buněčné linie; Pain Threshold; vysoká teplota; Action Potentials; In Vitro Techniques; Hot Temperature; NAV1.8 Voltage-Gated Sodium Channel; techniky in vitro; napětově řízený sodíkový kanál typ 11; napětově řízený sodíkový kanál typ 10; kůže; Evolution, Molecular; molekulární evoluce; Cell Line; Nociceptors; Skin; Patch-Clamp Techniques; NAV1.9 Voltage-Gated Sodium Channel; nociceptory; zvířata; metoda terčíkového zámku; Mice, Inbred C57BL; práh bolesti; akční potenciály; myši inbrední C57BL